Dexmedetomidine Alleviated Endoplasmic Reticulum Stress via Inducing ER-phagy in the Spinal Cord of Neuropathic Pain Model - Liu, Yongda; Wang, Shuang; Wang, Zhibin; Ding, Mengmeng; Li, Xingyue; Guo, Jiao; Han, Guang; Zhao, Ping (Frontiers in Neuroscience, 2020)
Studies demonstrated that spinal autophagy was impaired in spinal nerve ligation (SNL) rats. However, the relationship of endoplasmic reticulum (ER) stress and ER-phagy and whether dexmedetomidine (DEX) modulating ER-phagy remain unclear. In this study, male Sprague Dawley (SD) rats and SNL animal model were used. 4-phenylbutyric acid (4-PBA), tunicamycin (TM), rapamycin (RAP) and 3-methyladenine (3-MA) were intrathecal administrated respectively to demonstrate the relationship of ER stress and ER-phagy. Dexmedetomidine (30μg/kg/d) were administrated as treatment. Mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) tests were performed to evaluate nociceptive hypersensitivity. Proteins expressions were examined by Western blot, and the location of glucose-regulated protein 78 (Grp78) was examined by immunofluorescence staining. SNL induced ER stress, ER-phagy impairment. ER stress was altered in rostral ventromedial medulla (RVM); 4-phenylbutyric acid induced analgesic effect via inhibiting ER stress and unfolded protein response (UPR) pathways to induce ER-phagy; Tunicamycin led to worsen pain through enhancing ER stress and UPR pathways to further impair ER-phagy; Rapamycin provided analgesic effect through enhancing ER-phagy to relive SNL induced ER stress and UPR pathways activation; 3-methyladenine deteriorated pain via further impairing ER-phagy to aggravate ER stress; Dexmedetomidine provide analgesic effect through elevating ER-phagy. In conclusions, ER stress led to ER-phagy impairment in the spinal cord of SNL rats and participated in nociceptive descending system. ER-phagy impairment was both trigger and effector of ER stress via UPR pathways in SNL rats. Dexmedetomidine targeted ER-phagy to provide analgesic effect.